“No changes, but I become more positive mentally”: A mixed-methods study of the impact of a combined SEL and MBP on behavior change and academic achievement among Chinese adolescents - Wanying Zhou; Ros McLellan (Social and Emotional Learning: Research, Practice, and Policy)
This mixed-methods study aimed to investigate students' perspectives regarding their behavioral and academic changes following an 8-week combined intervention of Social and Emotional Learning (SEL) and Mindfulness-Based Program (MBP). A total of 552 teenagers (mean age = 13.03, SD = 0.50, 47.5% females) from an urban Chinese private school participated, with 184 participants randomly assigned to each condition (taught, self-help, and active control groups). Paired-sample t-tests were employed to examine changes within groups, while General Linear Models compared academic achievement changes among the three groups. Despite finding no significant improvement statistically on academic achievement, some students attributed their improved academic performance to the course. Thematic analysis was conducted on 115 written responses and 4 focus group interviews from the taught group. The analysis revealed several key themes among the Chinese population, including no changes, state change, attitude change, and behavior change. These themes were consistent with the theoretical foundations of Mindfulness-based Cognitive Therapy (MBCT) and aligned with previous qualitative research on Western adolescents. The study highlights the benefits of techniques and cognitive change in facilitating behavioral change and offers practical suggestions for supporting students in behaviour regulation. It also underscores qualitative research's role in detailing these practices' effects on behavior and academic performance. Furthermore, a proposed model aligns with established behavioral change theories, providing a practical visual aid for teachers. This study offers a comprehensive framework for future research on the theoretical constructs of MBPs and provides practical suggestions for supporting students in behavior regulation. Impact Statement: This study investigates SEL/MBPs in Chinese teenagers, revealing that mechanisms effective in Western contexts apply similarly here, and uncovers new themes enriching our SEL/MBPs understanding. It highlights qualitative research's role in detailing these practices' effects on behavior and academic performance. The findings offer educators practical tools for behavior regulation and lay a foundational framework for future SEL/MBP research, intervention designs, and strategies, signaling substantial potential for educational improvement.